2020
DOI: 10.1159/000509640
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Posterior Reversible Encephalopathy Syndrome due to Oral Tyrosine Kinase Inhibitor Cabozantinib: First Case Report

Abstract: We report here a rare case of atypical posterior reversible encephalopathy syndrome (PRES) due to oral tyrosine kinase inhibitor cabozantinib. No case reports of such have been found in our literature search. The patient, a 70-year-old female with metastatic renal cell cancer on oral tyrosine kinase inhibitor cabozantinib, was brought into the emergency room because of confusion and seizures, found to have elevated blood pressure and atypical MRI findings consistent with PRES due to cabozantinib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Previous studies suggested the timing was vague, ranging from weeks to months after initiation of this medication. 6,7 However, the timing of this presentation was similar to that of another TKI, imatinib, which was around 8–12 weeks. 4,5…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Previous studies suggested the timing was vague, ranging from weeks to months after initiation of this medication. 6,7 However, the timing of this presentation was similar to that of another TKI, imatinib, which was around 8–12 weeks. 4,5…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies suggested the timing was vague, ranging from weeks to months after initiation of this medication. 6,7 However, the timing of this presentation was similar to that of another TKI, imatinib, which was around 8-12 weeks. 4,5 The prognosis of toxic optic neuropathy varies, depending on the type of drug, drug dose, duration of drug usage, and time of diagnosis.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Two well-documented types of adverse events from these agents that present as encephalopathy are posterior reversible encephalopathy syndrome (PRES) and hyperammonemic encephalopathy. Multiple reports of adverse events related to PRES with the use of TKIs such as sorafenib, sunitinib, pazopanib, and cabozantinib have been reported in the literature, with the hypothesis that their anti-angiogenic properties can increase systemic blood pressure [ 15 ]. The underlying mechanism of TKI-induced hyperammonemic encephalopathy is poorly understood but has been well-documented across multiple therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to identify the underlying triggering factor when PRES is suspected since treatment is generally targeted toward correcting the triggering factor [4]. Chemotherapeutic agents being one of the triggering factors, several of them, as listed in Table 2, have been reported to be responsible for PRES including taxanes, platinum derivatives, vinca alkaloids, antimetabolites, anthracyclines, angiogenesis inhibitors, folate antagonists, and immunosuppressants [6]. However, the exact timeline of initiation of the chemotherapeutic agents and development of PRES has been varied across studies.…”
Section: Discussionmentioning
confidence: 99%